A. Pendahuluan Tindak pidana korupsi merupakan salah satu kejahatan non konvensional yang semakin populer dikalangan masyarakat. Dalam Undang-Undang Nomor 31 Tahun 1999 tentang Pemberantasan Tindak Pidana Korupsi sebagaimana diubah dengan Undang-Undang No - Dedy Saputra; Dodi Haryono; Mukhlis R (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Issues concerning policy lately quite a few are processed and charged under the Law of Corruption, giving rise to polemics. Polemic about whether or not charged with criminal policy, until now still leaves the issue. criminal liability a person against a crime that happened not in spite of the existence of the elements of criminal liability relating to the offense maker itself, which among others include the ability of responsible, errors in the broad sense and the absence of an excuse and justification. elements of error is the main element or a central element in criminal liability . Persons who have committed a criminal act can be held accountable for criminal conduct against him in a criminal act if it does have an element of error. State administration officials who make policy if the policy is set in an element of abuse of authority or policy behind the enactment of the law against these officials and have malicious intent (mistakes) intentionally want to earn a profit for themselves or others and may cause financial loss to the then state policymakers may be liable.